(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the effects of resistance training on post-ACL injury rehabilitation in basketball athletes. Methods: Integrative review, with a descriptive qualitative approach, together with the electronic databases: PUBMED, SCOPUS, WEB OF SCIENCE and PEDRO, using the keywords with the combination of Boolean operators: (“basketball athlete”) AND (“anterior cruciate ligament”) AND (“endurance training”) AND (rehabilitation). In the selection, the articles were included: Articles themselves and clinical trials from the last five years. Reviews, book chapters, congress abstracts were excluded. A total of 200 articles were found, in which three met the appropriate criteria to compose this systematic review. Results: Basketball players may need a greater training stimulus taking into account their sport-specific demands, injury mechanisms and biomechanical profiles, making a more adequate recovery from ACL injuries within the sport occur. Conclusion: Muscle conditioning should focus on rehabilitation programs mainly focusing on body weight, hip abductor strength and femoral anteversion, which are considered the main factors to be improved in the rehabilitation of ACL injuries in basketball players, making it athletes’ physical integrity is maintained, exposing them less to ACL injuries in the sports environment and keeping them in sport for a longer time at a high level.